2008
DOI: 10.2135/cropsci2008.01.0009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Soybean Rust‐Induced Yield Reduction

Abstract: Soybean rust (SBR; caused by Phakopsora pachyrhizi Syd. and P. Syd.) leads to premature leaf loss and yield reduction. The objectives of this study were to assess effects of SBR infection on soybean [Glycine max (L.) Merrill] yield and to identify causes for the yield reduction. Experiments were conducted in the 2005–2006 and 2006–2007 growing seasons at Londrina, Brazil. The five treatments were SBR infection beginning at either (i) the R2 or (ii) R5 growth stages; nondiseased defoliation treatments to mimic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 27 publications
2
52
0
12
Order By: Relevance
“…A recent study depicted a two-year field trial in Brazil where soybean rust was responsible for 37-67 % of soybean seed yield losses (Kumudini et al 2008). This study coincided with yield losses observed in Asia up to 80 % (Miles et al 2003).…”
supporting
confidence: 57%
“…A recent study depicted a two-year field trial in Brazil where soybean rust was responsible for 37-67 % of soybean seed yield losses (Kumudini et al 2008). This study coincided with yield losses observed in Asia up to 80 % (Miles et al 2003).…”
supporting
confidence: 57%
“…Long-term decreases in the expression of photosynthesis-related genes in compatible interactions would be consistent with observations of actual photosynthesis in P. pachyrhiziinfected soybean leaves. As P. pachyrhizi infection progresses, reduced photosynthesis and assimilation of CO 2 occur, due in part to defoliation and reduction of the green leaf area index as lesions form (Kumudini et al, 2008a). In addition, P. pachyrhizi also reduces the efficiency of photosynthesis in the remaining green tissues that visually appear to be healthy (Kumudini et al, 2008b).…”
Section: Nature Of the Differentially Expressed Genesmentioning
confidence: 99%
“…A ferrugem asiática é uma das mais agressivas doenças da soja, com dano entre 10% a 90% (Kumudini et al, 2008), e no Brasil vem provocando prejuízos desde 2001/02 pela falta de resistência genética e ampla área de semeadura (Yorinori et al, 2005;Godoy et al, 2009). Esta doença pode infectar a cultura a partir dos estádios iniciais de desenvolvimento e as condições ambientais são fundamentais no desenvolvimento das epidemias.…”
unclassified